Management Strategies for Patients With Epithelioid Hemangioendothelioma: Charting an Indolent Disease Course. (August 2021) - Yurkiewicz, Ilana R.; Zhou, Maggie; Ganjoo, Kristen N.; Charville, Gregory W.; Bolleddu, Sanjana; Lohman, Marti; Bui, Nam
Abstract : Background: Epithelioid hemangioendothelioma (EHE) is a malignant vascular neoplasm representing ∼1% of sarcomas. Due to its rarity, its clinical course is not well characterized and optimal treatment remains unknown. Materials and Methods: This was a retrospective review of patients with EHE treated at Stanford University between 1998 and 2020. Demographic characteristics, pathology results, treatment modalities, and clinical outcomes were collected from the electronic medical records. Results: A total of 58 patients had a mean age of 50.6 years and a slight female predominance (52%). Primary disease sites were liver (33%), soft tissue (29%), lung (14%), bone (9%), and mediastinum (9%). A majority (55%) had advanced or metastatic disease. Median overall survival (OS) was 16.9 years, with OS 89% at 1 year, 68% at 5 years, and 64% at 10 years. The longest median OS was associated with soft tissue sites and shortest with lung and mediastinal disease ( P =0.03). The localized disease had improved median OS compared with metastatic disease ( P =0.02). There was no OS difference between tumors >3 cm and those equal or smaller ( P =0.85). Surgery was a common treatment (71%), while radiation and ablation were sometimes used (28% and 9%, respectively). The median time to initiating therapy of any kind was 68 days. The median time to systemic therapy was 114 days. Conclusions: We report on the clinical characteristics and outcomes of patients with EHE at a large academic center. Treatment options included surgical excision, liver transplant, ablation, radiation, and systemic therapy. A subset of patients had indolent disease not requiring treatment upfront.